Intrapancreatic pseudoaneurysm causing massive gastrointestinal hemorrhage and chronic pancreatitis - Peynircioğlu, Bora; Karaosmanoğlu, Ali Devrim; İdilman, İlkay S. and Akata, Deniz and Şimşek, Halis (Turkish Journal of Gastroenterology, 2015)
Abstract Pseudoaneurysms of the splenic artery is a well-known complication of pancreatitis. However, to the best of our knowledge, a subcentimetric intrapancreatic pseudoaneurysm (without an associated pseudocyst) causing massive gastrointestinal bleeding and distal main pancreatic duct obstruction is a rare clinical phenomenon. Herein, we present such a unique complication with computed tomography images and subsequent successful endovascular treatment.